Heparin versus normal saline for the care of peripheral intravenous catheters in pediatrics: a meta-analysis of randomized controlled trials - Ran Li; Qiaoqi Zheng; Nengyue Chen; Li Zhao (BMC Pediatrics, 2024)
Abstract Background It is still controversial for neonates or children to choose normal saline or heparin solution in the care of peripheral intravenous catheters. This meta-analysis aimed to evaluate the effects of heparin versus normal saline for the care of peripheral intravenous catheters in pediatrics, to provide reliable evidence support for clinical care. Methods Two authors searched the PubMed, EMbase, Ovid Medline, Cochrane Library, Web of Science, CBM, WanFang Data and China National Knowledge Infrastructure (CNKI) databases for randomized controlled trial (RCT) of heparin versus normal saline for the care of peripheral intravenous catheters in pediatrics until July 16, 2023. The bias of risk tool recommended by Cochrane was used for the quality evaluation of included RCTs. Meta-analysis was carried out by using RevMan 5.4 software. Results A total of 22 RCTs involving 3988 peripheral intravenous catheters were finally included. Compare with normal saline, heparin could significantly increase the catheter indwelling time (MD = 9.10, 95%CI:3.30 ~ 14.90). Subgroup analysis indicated that for compare with normal saline, heparin could significantly increase the catheter indwelling time in the neonate (MD = 9.63, 95%CI: 0.38 ~ 18.88) and neonate + children population (MD = 6.22, 95%CI:2.72 ~ 9.73, P < 0.001). Heparin could significantly reduce the incidence of catheter-associated complications (RR = 0.84, 95%CI: 0.70 ~ 0.95). Subgroup analysis indicated that heparin could significantly reduce the incidence of catheter-associated complications in the neonate (RR = 0.70, 95%CI: 0.61 ~ 0.89). There was no publication bias amongst the synthesized outcomes by Egger’s test (all P > 0.05). Conclusions Heparin may be worthy of being applicated in the neonate population in terms of prolonged indwelling time and less complications. Limited by the evidence quality, more studies from different area and populations with rigorous design are needed to investigate the role of heparin versus normal saline for the care of peripheral intravenous catheters in pediatrics.